The Study of Parametric Applications in Indonesian Scientific Publications - Christanto, Ignatia Isabella Putri; Budhiyanto, Aris (Jurnal Indonesia Sosial Sains, 2026)
The development of discussions on the application of parametric architecture methods in scientific paper publications in Indonesia has increased over the last 10 years. This is greatly influenced by technological developments that have had an impact on helping visualise design ideas in the field of architecture. The purpose of this study is to analyse the development of the application of parametric architecture in Indonesia through data on the discussion of scientific papers published on Google Scholar in the last 10 years. The study also aims to determine how technology has been applied in the development of this method. With 86 publications related to the theme of discussion, the study employed bibliometric analysis methods and literature studies to help observe the purpose of the application and the use of digital technology. The results show that the majority of scientific publications are still concentrated in the context of conceptual design rather than constructive design. This study also highlights the potential for further research on parametric architecture in the use of parameters and algorithms for design exploration, shape optimisation, and material efficiency. These findings can be integrated with the context of local culture, climate, and the social needs of the Indonesian people.